Xác định tọa độ tuyệt đối bằng GPS trên WGS-84 - Hải, Vy Quốc; Tô, Trần Đình; Công, Dương Chí (Vietnam Journal of Earth Sciences, 2004)
Discussion on the absolute coordinates determinated by GPS in WGS-84